Vickers hardness of cast commercially pure titanium and Ti-6Al-4V alloy submitted to heat treatments - Da Rocha, Sicknan Soares [UNESP]; Adabo, Gelson Luis [UNESP]; Henriques, Guilherme Elias Pessanha; Nóbilo, Mauro Antônio de Arruda (FapUNIFESP (SciELO), 2006)
The purpose of this study was to evaluate the effect of heat treatments on the Vickers hardness of commercially pure titanium and Ti-6Al-4V cast alloys. Six-millimeter-diameter cylindrical specimens were cast in a Rematitan System. Commercially pure titanium and Ti-6Al-4V alloy specimens were randomly assigned to 3 groups (n=10) that received the following heat treatments: control (no heat treatment); treatment 1 (T1): heating at 750°C for 2 h; and treatment 2 (T2): annealing at 955°C for 1 h and aging at 620°C for 2 h. After heat treatments, the specimens were embedded in acrylic resin and their surface was ground and polished and hardness was measured. Vickers hardness means (VHN) and standard deviations were analyzed statistically by Kruskal-Wallis test at 5% significance level. For commercially pure titanium, Vickers hardness means of group T2 (259.90 VHN) was significantly higher than those of the other groups (control - 200.26 VHN and T1 - 202.23 VHN), which presented similar hardness means to each other (p>0.05). For Ti-6Al-4V alloy, statistically significant differences were observed among the three groups: T2 (369.08 VHN), T1 (351.94 VHN) and control (340.51 VHN) (p<0.05). The results demonstrated different hardness of CP Ti and Ti-6Al-4V when different heat treatments were used. For CP Ti, VHN means of T2 group was remarkably higher than those of control and T1 group, which showed similar VHN means to each other. For Ti-6Al-4V alloy, however, VHN means recorded for each group may be presented as follows: T2>T1>control.
Keywords: Heat treatments; Titanium; Vickers hardness